Analytical analysis of internal quantum efficiency with polarization fields in GaN-based light-emitting diodes. (November 2019) - Usman, Muhammad; Anwar, Abdur-Rehman; Munsif, Munaza; Malik, Shahzeb; Islam, Noor Ul
Abstract: This paper presents the analytical model for the analysis of internal quantum efficiency as well as light output power of GaN-based light-emitting diodes by introducing the polarization factor, which accounts for the polarization fields in the active region, in the standard ABC model. With the increase of the polarization, effective volume decreases which causes strong localization of carriers at lower potentials causing the carrier density to increase. This effect leads to loss mechanisms such as carrier leakage and Auger loss. Our theoretical analysis for internal quantum efficiency and light output power shows good agreement with the experimental results for both the blue and green InGaN light-emitting diodes. Highlights: A modified ABC model is proposed by incorporating polarization in the model. Our model shows good agreement with the experimental internal quantum efficiency of the devices. Our model also shows good agreement with the experimental light output power of the devices. Our model shows good agreement with the experimental efficiency of both the blue and green LEDs.